A Novel Analysis of CMAP Scans from Perspective of Information Theory: CMAP Distribution Index (CDIX) - Lu, Zhiyuan; Chen, Maoqi; Zong, Ya; Li, Xiaoyan; Zhou, Ping (IEEE transactions on biomedical engineering, 2023)
Objective: The compound muscle action potential (CMAP) scan is a useful technique for examination of neuromuscular disorders. The objective of this study is to develop a novel analysis of CMAP scans from the perspective of information theory. Methods: A novel index parameter called CMAP distribution index (CDIX) was developed to characterize CMAP scan based on calculation of the information entropy. The performance of CDIX was evaluated using CMAP scan data from healthy control and spinal cord injury (SCI) subjects, and compared with D50 and MScanFit motor unit number estimation (MUNE). Results: CDIX was significantly lower for the SCI subjects compared with the healthy control subjects (p < 0.001). A significant correlation (R 2 = 0.58, p < 0.001) was found between CDIX and MScanFit MUNE. Among all tested parameters (maximum CMAP, D50, MScanFit MUNE and CDIX), CDIX achieved the smallest relative width of the overlapping zone (WOZ%) between SCI and healthy control subjects. Conclusion: CDIX can be inferred as a useful index reflecting motor unit loss and muscle fiber reinnervation changes.